MIAC the study of erosion control - Mohamad Ashraf, Abd Latif (2018)
Conversion of land from forests to development has led to widespread deforestation, reducing the number of forests and the diversity of forests and wildlife. Despit e the fact that most of the land reduced to development, most fertile land is use for other purposes such as housing, recreation and industrial areas. Deforestation cause protected land to be exposed to various natural disasters. This is due to inability o f the forests to function as rain catchment areas. When heavy rains hit an area, the water descended on the surface and then eroded the soil into the river or any existing drain. This incident is mostly prefer in the case of landslides. This incident occurred due to the absence of plant roots that landed mainly on the cliffs or highlands. In July 2017, a flash flood had been observed in Lot 1210, Sultan Abdul Aziz Shah Airport Subang Selangor Darul Ehsan Malaysia. This research is to study the sediment transport and to compare the design size of sediment basin with the existing one. The failure of the design may affect the flash flood prediction.